Analisis Kelayakan Usaha Kerajinan Anyaman Kipas Rotan Di Desa Sungai Limas Kecamatan Haur Gading Kabupaten Hulu Sungai Utara - Azwar Saihani; Mislawati Mislawati (Rawa Sains: Jurnal Sains STIPER Amuntai, 2011)
Rattan as trunk rattan from for rattan mebel industries and rattan material product. This rattan product is much done in H.S.U regency. This research has the goals (i) To know how much fee that we need and how much will get the accepted. (ii) To know the properness of rattan the industrious of rattan plaited material. (iii) To know the appeared problem by the industrious of rattan fan plaited material craftsman in Sungai Limas Village. This research have been done in Sungai Limas Village Haur Gading Distric Hulu Sungai Utara Regency South Kalimantan. This research strated in April - June 2010. The result of the research were fixed cost Rp. 15.535,49,- per production, variable cost Rp. 91.911,32,- for once production, revenue Rp. 152.452,83,- for once production and RCR 1,42